Spectrophotometric Micro Determination of Gold by Formation of Ion Pair Association Complex with the Drug Ranitidine - Jasim, Fadhil; Al-Hamdany, Mohammed; Najim, Ahmed (Iraqi Journal of Science, 2025)
The drug ranitidine (N-[2-[[[5-[(dimethylamino) methyl] furan-2-yl] methyl]thio] ethyl]-N-methyl-2-nitroethene–1,1–diamine hydrochlorid) forms (λmax=260nm) ion-pair association complex with [AuBr4]-1 at pH range 2-3 extractable with 1,2-dichloroethane under the appropriate experimental conditions. A calibration plot was set up from which some analytical parameters are derived. These parameters include: linear dynamic range LDR (1-80μg.ml-1), RSD (1.9 %), sandell sensitivity (0.0360), detection limit (0.11ppm), Corr. Coef (r) (0.9988), recovery (98.32 %), Erel (-1.68 %) aqueous - to- organic phase ratio (5:4) and the mole-ratio method approved the [AuBr4]-1 : RAN as being 1:1 .